2018
DOI: 10.3389/fimmu.2018.02585
|View full text |Cite
|
Sign up to set email alerts
|

The Tumor Necrosis Factor Superfamily Members TNFSF14 (LIGHT), Lymphotoxin β and Lymphotoxin β Receptor Interact to Regulate Intestinal Inflammation

Abstract: Over 1.5 million individuals in the United States are afflicted with inflammatory bowel disease (IBD). While the progression of IBD is multifactorial, chronic, unresolved inflammation certainly plays a key role. Additionally, while multiple immune mediators have been shown to affect pathogenesis, a comprehensive understanding of disease progression is lacking. Previous work has demonstrated that a member of the TNF superfamily, TNFSF14 (LIGHT), which is pro-inflammatory in several contexts, surprisingly plays … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(38 citation statements)
references
References 30 publications
(47 reference statements)
1
37
0
Order By: Relevance
“…A recent study has nevertheless shown that interactions with tumor necrosis factor superfamily members (including Ltb) contribute to colitis in the DSS model. 77 We found that expression of Scl30a2 (coding for ZnT2) was upregulated in the ileum-suggesting an increase in Zn transport into secretory vesicles. Podany et al reported that ZnT2 is responsible for the accumulation of Zn in Paneth cell granules and that this accumulation is necessary for the cells' coordinated secretion and function in mice.…”
mentioning
confidence: 73%
“…A recent study has nevertheless shown that interactions with tumor necrosis factor superfamily members (including Ltb) contribute to colitis in the DSS model. 77 We found that expression of Scl30a2 (coding for ZnT2) was upregulated in the ileum-suggesting an increase in Zn transport into secretory vesicles. Podany et al reported that ZnT2 is responsible for the accumulation of Zn in Paneth cell granules and that this accumulation is necessary for the cells' coordinated secretion and function in mice.…”
mentioning
confidence: 73%
“…Intriguingly, several reports indicate that among stimulated pro-inflammatory cytokines, members of the Tumor Necrosis Factor (TNF) family are major players that participate in cancer progression [42,43]. Chronic intestinal inflammation is described to regulate expression and interaction of members of the TNF family such as TNF-α, TNF-β and LTβR acting as major mediators for CRC-related inflammation [44,45]. Moreover, our group has previously shown that TNF-β induces cancer progression and thus stimulates colorectal cancer cell malignity with the same potency as TNF-α [16,18,46].…”
Section: Discussionmentioning
confidence: 99%
“…The other receptor, LTβR, is found on the surface of epithelial, stromal, immature DC, and myeloid cells, but not on lymphocytes (14). During normal biological development LIGHT-LTβR interactions have been identified as a component of lymphoid structure development and maintenance (15).…”
Section: Lightmentioning
confidence: 99%